Analisis Frasa Nomina pada Berita Kesehatan dalam Surat Kabar Suara Merdeka di Bulan September 2024 - Dwi Amalia Nur Rahmawati; Tammah Candramurti Estiningtyas; Neiska Indah Nurbaeti; Laila Faizatus Saffana; Stivany Gracea Gibrania; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Ahmad Ripai (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This article discusses the use of noun phrases in health news in Suara Merdeka newspaper in September 2024. The purpose of writing this article is to identify the use of noun phrases by analyzing the types of noun phrases in depth, research data along with an explanation of the types of phrases based on modificative noun phrases, coordinative noun phrases, and appositive noun phrases. The research method in writing this article uses a descriptive method, a theoretical approach to language, based on data collection using the simak catat technique, and using agih analysis to select data in the study. This research uses informal and formal data presentation techniques delivered in narrative or explanatory form, and presented in tabular form. The result of this research shows some discussion: (1) Identification of modificative noun phrases found as much as 29 data, (2) Identification of coordinative noun phrases found as much as 3 data, (3) Identification of appositive noun phrases found as much as 2 data. This research is expected to be useful as a learning medium, especially in the syntactic field unit, namely noun phrases.